PARADIGMAL CONCEPT OF THE MOBILITIES IN THE CONTEXT OF GLOBALIZATION: PHILOSOPHICAL EXPOSITION - Kateryna Lobanova ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The article examines the main sources of globalization, formulates the modern paradigm of world mobilities, as well as demonstrates their relationship with each other. The modern process of regular changes and the creation of a new paradigm of reality is substantiated.